AntiMüllerian Hormone Level in Laparoscopic Cystectomy - Edwin Budipramana; Nusratuddin Abdullah; Telly Tessy (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To evaluate the impact of laparoscopic cystectomy using cautery and suturing technique on the ovarian reserve represented by the level of Anti-Müllerian Hormone (AMH) serum. Method: This used prospective cohort study design conducted in Dr. Wahidin Sudirohusodo Hospital, Department of Obstetrics and Gynecology, Faculty of Medicine Universitas Hasanuddin, Makassar, from November 2014 to October 2015. We got total samples of 60 subjects divided into cautery and suturing group. Anti-Mullerian hormone serum test was examined on all subjects pre and post laparoscopic cystectomy. Result: The result indicated a significant decrease of AMH level undergoing laparoscopic cystectomy both cautery and suturing technique; whereas, more dominant results were showed in the cautery group (p0.05). Conclusion: The decline in the number of ovarian reserve as described by the reduction of AMH level occurs significantly in both cauterization and suturing technique, which are more dominant reduction in the cauterization group. [Indones J Obstet Gynecol 2016; 4-4: 203-207] Keywords: Anti-Müllerian Hormone, laparoscopic cystectomy, ovarian reserve